2022
DOI: 10.3390/nano12234156
|View full text |Cite
|
Sign up to set email alerts
|

Effective Thallium(I) Removal by Nanocellulose Bioadsorbent Prepared by Nitro-Oxidation of Sorghum Stalks

Abstract: Thallium(I) (Tl(I)) pollution has become a pressing environmental issue due to its harmful effect on human health and aquatic life. Effective technology to remove Tl(I) ions from drinking water can offer immediate societal benefits especially in the developing countries. In this study, a bio-adsorbent system based on nitro-oxidized nanocellulose (NOCNF) extracted from sorghum stalks was shown to be a highly effective Tl(I) removal medium. The nitro-oxidation process (NOP) is an energy-efficient, zero-waste app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Cellulose nanomaterials (nanofibers, nanocrystals, nanoparticles) are used in various wastewater treatment applications (Sjahro et al, 2021;Chen et al, 2022). Cellulose nanocrystals (CNCs) are commonly extracted from cellulose sources, including a diverse range of woods such as pine, birch, oak, and Cassava (Egbosiuba, 2022), as well as from other biological materials like bacteria, algae, tunicates, and more (Sharma et al, Frontiers in Chemistry frontiersin.org 2019; Jeevanandam et al, 2021).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…Cellulose nanomaterials (nanofibers, nanocrystals, nanoparticles) are used in various wastewater treatment applications (Sjahro et al, 2021;Chen et al, 2022). Cellulose nanocrystals (CNCs) are commonly extracted from cellulose sources, including a diverse range of woods such as pine, birch, oak, and Cassava (Egbosiuba, 2022), as well as from other biological materials like bacteria, algae, tunicates, and more (Sharma et al, Frontiers in Chemistry frontiersin.org 2019; Jeevanandam et al, 2021).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…Although certain biomass resources, such as jute fiber, spinifex grass, bamboo cellulose [28], moringa plant [33], and sorghum stalk [37], were used for the preparation of CCNF, considerable research on banana peel has never been reported before. As a result, the current work explored this abundant waste for one-pot preparation of carboxyl cellulose nanofibers using the nitro-oxidation method.…”
Section: Introductionmentioning
confidence: 99%